Pengaruh Inflasi, Nilai Tukar, Ekspor dan Impor terhadap GDP di Negara Belgia - Andi Triyawan; Amatullah Nur Afifah (Universitas Batanghari Jambi, 2023)
This study aims to analyze the effect of exchange rates, inflation, exports and imports on economic growth in Belgium for the period 2002-2020. The method used in this research is multiple linear regression with f test and partial test. Exchange rate data is taken from the CBR (Central Bank of Russia), GDP, exports and imports data is taken from the world bank, and inflation data is taken from the IMF. The results show that inflation, exchange rate, exports and imports together have a positive effect on GDP in Belgium. Partially, the inflation rate has a significant negative effect on GDP, the exchange rate has a positive and significant effect on GDP, while exports and imports have no significant effect on GDP.